Chronic exposure to a pervasive pharmaceutical pollutant erodes among-individual phenotypic variation in a fish. (August 2020) - Tan, Hung; Polverino, Giovanni; Martin, Jake M.; Bertram, Michael G.; Wiles, Sarah C.; Palacios, Maria M.; Bywater, Candice L.; White, Craig R.; Wong, Bob B.M.
Abstract: Pharmaceutical pollution is now recognised as a major emerging agent of global change. Increasingly, pharmaceutical pollutants are documented to disrupt ecologically important physiological and behavioural traits in exposed wildlife. However, little is known about potential impacts of pharmaceutical exposure on among-individual variation in these traits, despite phenotypic diversity being critical for population resilience to environmental change. Furthermore, although wildlife commonly experience multiple stressors contemporaneously, potential interactive effects between pharmaceuticals and biological stressors—such as predation threat—remain poorly understood. To redress this, we investigated the impacts of long-term exposure to the pervasive pharmaceutical pollutant fluoxetine (Prozac®) on among-individual variation in metabolic and behavioural traits, and the combined impacts of fluoxetine exposure and predation threat on mean metabolic and behavioural traits in a freshwater fish, the guppy ( Poecilia reticulata ). Using a mesocosm system, guppy populations were exposed for 15 months to one of two field-realistic levels of fluoxetine (nominal concentrations: 30 and 300 ng/L) or a solvent control. Fish from these populations were then tested for metabolic rate (oxygen uptake) and behaviour (activity), both before and after experiencing one of three levels of a predation treatment: an empty tank, a non-predatory fish ( Melanotaenia splendida ) or a predatory fish ( Leiopotherapon unicolor ). Guppies from both fluoxetine treatments had ∼70% lower among-individual variation in their activity levels, compared to unexposed fish. Similarly, fluoxetine exposure at the higher dosage was associated with a significant (26%) reduction in individual-level variation in oxygen uptake relative to unexposed fish. In addition, mean baseline metabolic rate was disrupted in low-fluoxetine exposed fish, although mean metabolic and behavioural responses to predation threat were not affected. Overall, our study demonstrates that long-term exposure to a pervasive pharmaceutical pollutant alters ecologically relevant traits in fish and erodes among-individual variability, which may be detrimental to the stability of contaminated populations globally. Graphical abstract: Image 1 Highlights: We exposed female guppies ( P. reticulata ) to fluoxetine and acute predation threat. Fluoxetine reduced among-individual variation in both metabolic rate and activity. Fluoxetine caused a non-monotonic reduction in baseline metabolic rate. Fluoxetine did not affect metabolic and behavioural responses to predation threat.